Male Dominance in the Mirrors of Women's Creativity the Poetic Discourse of the Poets of the Abbasid Era as a Model (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research deals with the reflections of masculine dominance in the mirrors of the poetic discourse of the poets of the Abbasid era in an attempt to read this discourse a deconstructive cultural reading, that sheds light on the textual investigations of male domination, and its effects on the process of creativity, in the production of the female voice framed by the space-time dimension of the Abbasid era, and the authoritarian political and cultural system dominant in its character Patriarchy.   The female voice proves in its creatively unequal battle, like the female’s battles in other contexts, its creative brilliance in the remaining few that escaped from the grip of the male censor, passing to us exhausted from neglect. The truth is that this remaining creative poetic discourse of the female voice rivals its male counterpart at the very least, if we do not say that it surpasses it in many cases, so that the absence of the poetic female voice is the most prominent manifestation of male domination on the axis of quantity, while that domination casts its shadows on the surviving discourse of legacy. Women’s creativity, and its features appear clear through textual realizations, the most prominent of which is the virile focus with its structural and visionary levels, or in other words, the levels of apparent structural formations, and the deep essential visions on which the entire textual structure is based.   The research also seeks to trace the path of the graphic pattern, and its frequencies between stability and transformation, compliance and rebellion. And revealing the masculine pattern, the frequencies of its dominance, intensity and severity. Also, it follows the textual representations, and its effects on the artistic and human experience of the female voice.